2023
DOI: 10.1302/0301-620x.105b7.bjj-2022-1058.r2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing patient-reported outcomes following periacetabular osteotomy and open osteochondroplasty in the setting of borderline hip dysplasia

Abstract: AimsThis study reports mid-term outcomes after periacetabular osteotomy (PAO) exclusively in a borderline hip dysplasia (BHD) population to provide a contrast to published outcomes for arthroscopic surgery of the hip in BHD.MethodsWe identified 42 hips in 40 patients treated between January 2009 and January 2016 with BHD defined as a lateral centre-edge angle (LCEA) of ≥ 18° but < 25°. A minimum five-year follow-up was available. Patient-reported outcomes (PROMs) including Tegner score, subjective hip value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Thus far, only a few studies have reported on functional outcomes after PAO. 4 , 19 , 21 Even though all of these studies reported improvements in radiographical parameters and patient-reported outcomes, none included an analysis of sports activity. Andronic et al 4 described significantly improved Tegner activity scores after PAO in a cohort of 53 hips in 42 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, only a few studies have reported on functional outcomes after PAO. 4 , 19 , 21 Even though all of these studies reported improvements in radiographical parameters and patient-reported outcomes, none included an analysis of sports activity. Andronic et al 4 described significantly improved Tegner activity scores after PAO in a cohort of 53 hips in 42 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 19 , 21 Even though all of these studies reported improvements in radiographical parameters and patient-reported outcomes, none included an analysis of sports activity. Andronic et al 4 described significantly improved Tegner activity scores after PAO in a cohort of 53 hips in 42 patients. However, no detailed information on return to sports and changes in physical activity was found in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations